The Influence of Pseudorange Smoothing Time in GBAS under Ionospheric Scintillation - da Costa Silva, Weverton [UNESP]; da Silva, Crislaine Menezes [UNESP]; de Souza, Felipe Tintino Linhares [UNESP]; Monico, João Francisco Galera [UNESP]; Tsuchiya, Ítalo [UNESP]; Caccioppoli, Natali (Institute of Navigation, 2023)
One of the challenges in using GBAS at low latitudes is to minimize the effects of the ionosphere on GNSS signals. In this region, the occurrence of phenomena such as ionospheric scintillation can affect the availability of satellites used for positioning. GBAS uses pseudorange smoothed measurements, which the filter must be restarted whenever satellite measurements are affected by ionospheric scintillation. Using a filter with a smoothing time constant of 100 s, a satellite could go up to 6 min without contributing to the positioning solution. In a scenario of strong ionospheric scintillation, in which many satellites can be affected, this can make the use of GBAS unfeasible for some time. Therefore, in this study, we evaluate the performance of GBAS in scenarios where the smoothing time constant is reduced under conditions of ionospheric scintillation. The processing used data from three days (DOYs 072 to 074/2023) with the occurrence of ionospheric scintillation, at 4 GNSS stations of the INCT GNSS NavAer Network located in Presidente Prudente (Brazil). Of these, three stations were defined as reference stations, and the fourth station was defined as an aircraft in the static mode. Processing was performed using the PEGASUS software developed by EUROCONTROL in GAST C and D modes for smoothing time constants of 0, 10, 30, and 100 s. The results showed that the solution without pseudorange smoothing (0 s) generated the highest number of GBAS positioning solutions. However, in terms of quality, these unsmoothed solutions were noisier compared to those with other smoothing time constants.